Limitations of DEA-based approach and alternative methods in the measurement and comparison of social efficiency across firms in different transport modes: An empirical study in Japan - Oum, Tae Hoon (2015)
This paper measures and compares social efficiency of railway firms and airlines in Japan’s domestic intercity travel market. Unlike other efficiency studies, our input and output measures are more comprehensive because we incorporate the life-cycle CO2 emissions as an undesirable output and travelers’ time and government spending on air infrastructure as inputs. We use the nonparametric directional output distance function (DODF) together with the composite social efficiency index to analyze the yearly panel data of the three major railroads and two major airlines during 1999–2007. The results indicate that the railroads are more socially efficient than airlines. Furthermore, we discuss the inability of nonparametric DODF method for comparing the social efficiency of firms across modes.